Who Does What? The Distribution of Housework and Childcare in Portuguese Families - Mariana Pinho; Inês Lourenço; Marisa Lousada (Genealogy, 2025)
An increasing number of studies have sought to explore the gender gap in the distribution of family responsibilities. While men and women have become more similar in their egalitarian views and involvement toward paid work and family responsibilities, mothers continue to bear the brunt of housework and caregiving responsibilities. The present study explored the allocation of family work among Portuguese couples and the social–psychological characteristics associated with it. A sample of 153 parents with young children completed questionnaires. The results revealed that parents’ gender ideologies and biological essentialism were related and predicted their involvement in childcare and housework. Overall, the findings shed light on the mechanisms that shape the division of childcare and housework and suggest pathways for achieving greater gender equality within the home.